Investigation of Galactinol Synthase Genes in Plant Defense Mechanisms against Adverse Environmental Conditions in Hot Pepper (Capsicum annuum) - Ngoc Thi Bich Chu; Ha Duc Chu; Phi Bang Cao; Cuong Ba Cao (Bogor Agricultural University, Indonesia, 2026)
The galactinol synthase (GolS) and raffinose synthase (RS) play crucial roles in the synthesis of raffinose family oligosaccharides, which are involved in stress protection, carbohydrate transport, and fruit development in plants. This study aimed to conduct a genome-wide identification and characterization of GolS and RS genes in hot pepper (Capsicum annuum) and to investigate their responses to environmental and hormonal factors. Six CaGolS and seven CaRS genes were identified in the pepper genome. Structural analysis showed that CaGolS genes have relatively compact exon-intron arrangements, while CaRS genes possess more complex structures. Phylogenetic comparison with related species revealed strong evolutionary conservation within the Solanaceae group. Transcriptome analysis showed that CaGolS1, CaGolS2, CaGolS3, CaRS2, and CaRS7 were highly responsive to abiotic stresses such as cold, heat, salinity, and osmotic stress, as well as to hormonal treatments involving abscisic acid, jasmonic acid, salicylic acid, and ethylene. Several genes also showed differential expression during fruit development and ripening, indicating their contribution to sugar metabolism and stress adaptation during maturation. The results provide new insights into the GolS and RS gene families in hot pepper and identify potential gene targets for developing stress-tolerant and high-quality pepper cultivars.